Comprehensive analysis of complete Chloroplast genome sequence of Cardiospermum halicacabum L. (Sapindaceae) - Yongjing Su; Wei Wei; Lintong Han; Haicheng Wen; Hailin Lu (Scientific Reports)
Abstract Cardiospermum halicacabum L., a notable species of the genus Cardiospermum, is well-known for its culinary and medicinal properties. Nonetheless, a detailed description of the C. halicacabum chloroplast’s phylogeny and genes is still absent. We present the findings of an in-depth investigation of the chloroplast genome of C. halicacabum. The circular, 159,370 bp chloroplast genome of C. halicacabum has a 37.91% GC content. There are 134 genes in the circular genome, comprising 89 protein-coding genes, 37 tRNAs, and 8 rRNAs. There are 28 repeats of a simple sequence. A comparison of the chloroplast genomes of five related species reveals differences in the contraction and expansion of the reverse repeat region between C. halicacabum and other Sapindaceae. Our phylogenetic study reveals that C. halicacabum has a close connection with S. erecta. The chloroplast genome of C. halicacabum has been studied, which has helped us better understand the evolutionary links among Sapindaceae species.